Parents' Roles and Perceptions Towards their Children in Online English Learning - Ferina Milenia Amir; Yuna Tresna Wahyuna; Praditya Putri Utami (Edumaspul: Jurnal Pendidikan, 2022)
This research aims to investigate parents’ roles and perceptions towards their children in online English learning during covid-19. The data from six participants of the parents from Junior High School were collected through questionnaires and semi-structured interviews. The result showed that parents' roles in helping their children in online English learning during covid- 19 including parents as teacher, parents as facilitator, parents as motivator and parents as directors. Regarding parents' perception of children's English learning viewed from their experiences and challenges, parents showed negative and positive perceptions. In addition, some of the challenges of parents in accompanying children to learn English online, namely parents have limited time, lack of understanding learning materials and the unwillingness of children to follow English learning.